A Quantitative Analysis of Research Trends and Thematic Development in Derivational Morphology - Nugraha, Danang Satria (Journal of Languages and Language Teaching, 2025)
Derivational morphology is crucial for understanding the organization of language and dynamics of vocabulary expansion. Despite extensive research in this area, a data-driven analysis of research trends and thematic development has been lacking. This study aims to address this gap by employing a scientometric approach to analyze publications on derivational morphology from 2014 to 2024. Utilizing the Scopus database, a corpus of 370 English-language publications was compiled and analyzed using VOSviewer software. The findings reveal a steady growth in yearly output, with an average of 34 publications per year. Network visualization of keyword co-occurrence identified five prominent thematic clusters: (1) core morphological concepts (22.78%), (2) morphology-semantics interface (20.14%), (3) morphology-syntax interface (19.44%), (4) psycholinguistic perspectives (18.06%), and (5) cognitive aspects of word recognition (14.58%). Collectively, these cluster illuminate the evolving landscape of derivational morphology research, highlighting key areas for future investigation, particularly at the interfaces with semantics, syntax, and cognition. The study’s findings therefore offer guidance for shaping future research trajectories and developing comprehensive morphology curricula that reflect the field’s nature.